TEOLOGI HINDU DALAM YOGA SURYA DHARYAM TRADISI WATUKARU DI PASRAMAN SERULING DEWATA TABANAN BALI : TEOLOGI HINDU DALAM YOGA SURYA DHARYAM TRADISI WATUKARU DI PASRAMAN SERULING DEWATA TABANAN BALI - yunitri, arik; Magister, I Gusti Made Widya Sena; Magister, Ni Wayan Sariani Binawati (Pangkaja: Jurnal Agama Hindu, 2026)
Divine Science (theology), the search for truth and self-perfection is the main goal, which can be achieved through a deep understanding of the holy scriptures and appropriate spiritual practices, so as to create harmony and harmony between the mind, body and soul. The practice of yoga is one way to achieve spiritual goals, and the Watukaru Tradition Surya Dharyam Yoga is a unique and not widely known form of yoga. Therefore, proper explanation and delivery is needed so that Surya Dharyam Yoga can be understood and well accepted by the public. This research aims to examine the Watukaru Tradition of Surya Dharyam Yoga from the perspective of Hindu theology at Pasraman Seruling Dewata, Tabanan, Bali, with a focus on three main aspects: the form of Surya Dharyam Yoga, the meaning of Hindu theology contained in it, and the implications of yoga practice for students. Thus, this research can provide a deeper understanding of the Watukaru Tradition of Surya Dharyam Yoga and its relevance in a Hindu spiritual context. This research uses a theoretical framework consisting of Structural Functional Theory, Religious Theory, and Healthy Theory to comprehensively analyze and understand the Surya Dharyam Yoga of the Watukaru Tradition. Surya Dharyam Yoga is a unique yoga practice developed at Pasraman Seruling Dewata, which focuses on worshiping Dewa Surya (Sun God) at sunrise. This practice consists of 12 movements that begin with prayer and supplication, and emphasizes the harmonious relationship between humans and nature. Surya Dharyam Yoga also reflects the principles of Hindu theology, such as the concept of Dharma, which aims to achieve balance of body, mind and spirit, as well as increasing self-awareness and harmony with nature. Thus, Surya Dharyam Yoga is not only beneficial for physical and mental health, but also for spiritual growth and awareness of connectedness with nature. Keywords: Surya Dharyam Yoga, Hindu Theology.